Article Retrieval And Automatic Summarization System Using BERT-Based Neural Network Model On Chatbot - Awaluddin, Muhammad Ghazali; Aksa, Muhammad; Arifky, Reza; Bakri, Muhammad Fajar; Surianto, Dewi Fatmarani; Edy, Marwan Ramdhany; Zain, Satria Gunawan (Jurnal Teknik Informatika (Jutif), 2026)
The rapid growth of online scientific publications presents challenges in efficiently filtering relevant information. Many search systems still rely on keyword matching, which is often ineffective in understanding the context of user queries. This study develops a chatbot system based on BERT (Bidirectional Encoder Representations from Transformers) for scientific article retrieval and automatic summarization. The system is designed to comprehend user intent and generate summaries of relevant articles. The evaluation was conducted on a dataset of 506 scientific articles, assessing search accuracy based on topic, abstract, author name, and time range. Results show 100% accuracy in searches by author and abstract, with varying performance in topic-based and time-based searches. This system is expected to enhance the efficiency and relevance of scientific literature retrieval and support the productivity of researchers across various fields.